2022
DOI: 10.3390/ma15217545
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Plastic Deformation on the Microstructure and Tensile Strength of Haynes 282 Nickel Superalloy Produced by DMLS and Casting

Abstract: The article presents the results of research on the influence of plastic deformation on the microstructure and tensile strength of Haynes 282 nickel superalloy produced by direct metal laser sintering (DMLS) and a conventional technique (casting). Samples were tested for dimensional accuracy using a 3D scanner. Then, the samples were subjected to plastic deformation by rolling. The microstructures of the DMLS and the as-cast samples were analysed using a scanning electron microscope. The strength properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Tensile tests were conducted at an initial strain rate of 10 −3 s −1 using a Zwick/Roell Z005 (Zwick GmbH & Co. KG, Ulm, Germany) testing machine equipped with a 1 kN load cell. Digital image correlation (DIC) system was used for strain measurements which has been described more in detail in [ 27 , 28 ]. Based on the obtained stress–strain curves, the strain-hardening rate Θ was calculated as Θ = dσ/dε where σ and ε are a true stress and true strain, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Tensile tests were conducted at an initial strain rate of 10 −3 s −1 using a Zwick/Roell Z005 (Zwick GmbH & Co. KG, Ulm, Germany) testing machine equipped with a 1 kN load cell. Digital image correlation (DIC) system was used for strain measurements which has been described more in detail in [ 27 , 28 ]. Based on the obtained stress–strain curves, the strain-hardening rate Θ was calculated as Θ = dσ/dε where σ and ε are a true stress and true strain, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Sarraf et al 10 discussed a three-stage coating formation mechanism during reactive air aluminising in a Ni-base superalloy, and the aluminide coating of pack cementation was decided by the aluminium activity, especially the aluminising temperature and time. 11 The low-activity aluminide coating deposited at high temperatures always possessed a thick double-layered structure, 12 whilst a low depositing temperature of high activity resulted in a triple-layered coating structure in which a middle layer consisting of β-NiAl phase without precipitates due to the inward diffusion of Al. 13 Yener et al 14 demonstrated that the macroscopic layer thickness of the IN738 alloy was significantly increased with increasing temperature owing to a higher diffusion rate.…”
Section: Introductionmentioning
confidence: 99%
“…Laser Beam Powder Bed Fusion manufacturing techniques (LB-PBF), for example, Selective Laser Melting (SLM) or Direct Metal Laser Sintering (DMLS), are increasingly used in the producing of metallic parts from various alloys, such as Ni-based superalloys, stainless steels or titanium materials [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. These processes in which layer after layer of metal powder are selectively melted by the interaction of a high energy density laser beam offer many advantages over conventional manufacturing methods.…”
Section: Introductionmentioning
confidence: 99%
“…The negative effects are mainly caused by the crystallographic texture, the structure of melt pools, the privileged distribution of certain phases and carbides, and the presence of asymmetrical defects [ 19 , 20 ]. Boswell et al in their study [ 20 ] showed that the anisotropic effect could be effectively reduced with appropriate dissolution and ageing heat treatment, leading to recrystallization and local texture reduction.…”
Section: Introductionmentioning
confidence: 99%